RESPON PERTUMBUHAN DAN HASIL JAMUR TIRAM PADA KONSENTRASI NPK DAN FREKUENSI PENYIRAMAN - Sri Mulatsih; Asfaruddin Asfaruddin (University of Prof. Dr. Hazairin, SH, 2020)
This research to determine the concentration and frequency of watering on growth and yield of Oyster Mushrooms. The Research used a Randomized Method with two factors, The first factor was NPK concentration which consisted of 3 level : A1 = 0 %, A2 = 10%, A3 = 30 % and the second factor was the frequency of watering consisting of 3 level, B1 : 1 time, B2 : 2 time, B3 : 3time. The result showed that the NPK concentration treatment had a significant KONSENTRASI affected on mushroom 12 week after plant, significantly affected of mushroom/baglog and weight of mushroom/baglog 12 week after plant, but no significant effect weight on mushroom 8 week after plant. The frequency of watering had significant effect of amound mushroom/baglog and weigth mushroom 12 week after plant, significantly effect on the weigt mushroom/baglog 8 week after plant and had no significant effection other parameter. The interaction between the NPK concentration and frequency of watering only had significant effected the weight of mushroom 8 week after plant. Concentration NPK10 % (A2) and 2 times watering frequency (B2) showed the best oyster mushroom result.